2023
DOI: 10.3389/fnut.2022.1114149
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Probiotics and constipation

Abstract: Editorial on the Research TopicProbiotics and constipation This Research Topic mainly focuses on the attenuation effect and potential mechanism of new probiotics on constipation. To date, five papers, including four research articles and one review article have been collected in this Research Topic. Bacillus coagulans BC01, Bifidobacterium lactis TY-S01, and Lactobacillus plantarum KFY02 increased the fecal moisture and gastrointestinal transit rate in mice (Zhou et al., Tang et al. and Yi et al.). Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The study revealed that the intake of probiotics in children with FC significantly improved treatment success. However, no significant association was detected between probiotics intake and frequency of abdominal pain, stool consistency, defecation pain, and fecal incontinence [34]. So, conflicting findings of previous reviews probably resulted from methodologic errors, and the evidence available thus does not support using probiotics as a single or coadjuvant therapy for treating FC in children [35].…”
Section: Probioticsmentioning
confidence: 92%
“…The study revealed that the intake of probiotics in children with FC significantly improved treatment success. However, no significant association was detected between probiotics intake and frequency of abdominal pain, stool consistency, defecation pain, and fecal incontinence [34]. So, conflicting findings of previous reviews probably resulted from methodologic errors, and the evidence available thus does not support using probiotics as a single or coadjuvant therapy for treating FC in children [35].…”
Section: Probioticsmentioning
confidence: 92%